Creating social value and community impact in the Third Sector: A case study of the O.D.V. Stella Cometa (European journal of volunteering and community-based projects, 2025)
Despite growing academic interest in Third Sector Organizations (TSOs), objective difficulties remain in assessing the social value these organizations create. This research explores how small TSOs can generate social value within local communities, focusing on a small volunteer-based organization (O.D.V.), Stella Cometa, based in Cosenza, Southern Italy. Using a qualitative case study methodology, we collected primary data (semi-structured interviews administered to board members) and secondary data (official documents, social and financial reports, and journalistic sources) to examine the organization’s activities and programs. The findings show that Stella Cometa creates social value in four main areas: education, healthcare, disability support, and women’s economic empowerment. However, critical challenges persist, particularly concerning impact measurement and stakeholder collaboration. This study offers both practical and theoretical insights into the multidimensional contribution of small TSOs in local contexts.